2014
DOI: 10.1080/03602559.2014.891236
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Amorphous Morphology in Physical Properties of Ultra High Molecular Weight Polyethylene

Abstract: The role of amorphous layer in the physical properties of ultra high molecular weight polyethylene (UHMWPE) was investigated. It revealed that the thicker amorphous layer would promote the toughness of polyethylene, but make a negative effect on the rigidity of the polymer. Furthermore, it would be easier for semicrystalline polymers with less entangled chains to bring out the interlamellar slippage that would absorb more energy during the deformation. Finally, promotion of the physical properties of UHMWPE wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Figure shows that the calculated crystallinity goes down from 0.66 to 0.46 with the weight fraction of long chains at the end of isothermal treatment because long chains make it more difficult for the polymer chains to crystallize from the entangled melts. This is consistent with Li et al who reported that the crystallization enthalpy (Δ H c ) would decrease with the increased molecular weight. Krumme et al have also drawn a conclusion that the fully achieved crystallinity decreases linearly with the molecular average weight in their experimental study of bimodal MWD PE.…”
Section: Resultsmentioning
confidence: 93%
“…Figure shows that the calculated crystallinity goes down from 0.66 to 0.46 with the weight fraction of long chains at the end of isothermal treatment because long chains make it more difficult for the polymer chains to crystallize from the entangled melts. This is consistent with Li et al who reported that the crystallization enthalpy (Δ H c ) would decrease with the increased molecular weight. Krumme et al have also drawn a conclusion that the fully achieved crystallinity decreases linearly with the molecular average weight in their experimental study of bimodal MWD PE.…”
Section: Resultsmentioning
confidence: 93%
“…This indicates that the catalytic ash presents less influence on the crystallization of UHMWPE since the ash usually has an irregular shape and random distribution caused by the fragmentation of supports . Interestingly, the polymer with the weakly entangled state (PE-POSS-0.8) presents an exceptional impact strength owing to its amorphous microstructure , (see Figure a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…As the π‐stacking distance decreases from 3.8 to 3.5 å, the mobility of the resulting transistor increases from ~10 −4 to 0.4 cm 2 V −1 s −1 . Another way to tune interchain interactions is through heteroatom substitution . With a series of naphthalenediimide‐based copolymers, Zhao et al .…”
Section: Opportunities For Improving Charge Transportmentioning
confidence: 99%